Identifying the impact of mutagenic active environmental impact on human body in Riwne - Grygus, Igor; Kaskiv, Mariana (Journal of Education, Health and Sport, 2017)
<span style="font-size: 14pt; line-height: 150%; font-family: 'Times New Roman', serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">The aim of this work was to evaluate the mutagenicity of the natural environment using the MNA-test in Riwne. <span style="font-size: 14pt; line-height: 150%; font-family: 'Times New Roman', serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">A mutagenic environmental activity study was performed. Equal to the use of the MJA test, which reports one of the contemporary monitoring methods for assessing environmental contamination by harmful toxins of anthropogenic origin and their effect on genetic health of the population. According to the results of the level of the mutagenic background of the territories of the studied cities and the MJA-index of mucosal cells vacuoles (children of the preschool age of the city according to the surveyed indicators can be arranged in the next growing number of: Nikita > Riwne > Chernivtsi > Dnipropetrovsk > Yellow Water.